2000
DOI: 10.1111/1528-3577.00018
|View full text |Cite
|
Sign up to set email alerts
|

Rereading the Public: Isolationism and Internationalism Revisited

Abstract: This is the first installment in what we hope will be a recurring series of Forums in ISP.In each segment we intend to provide an outlet for peer-reviewed dialogue and debate on important topics in the field and to allow our readers to discuss material previously printed in the pages of ISP. Below are two comments on "Challenging U.S. Policymakers' Image of an Isolationist Public" by Steven Kull and Clay Ramsay published in ISP 1:1. Both comments raise a number of important issues pertaining to the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Protests have certainly influenced perceived opinion, and trade policy officials are addressing some of the concerns raised by civil society organizations, which is no doubt wise. 3 Yet many elites may have misperceived the state of mass opinion, something that is quite common in the area of international affairs (Kull and Destler 1999;Kull and Ramsay 2000;Page and Barabas 2000;Clark et al 2000). Our data show that the permissive consensus on trade continues and that mass opinion is supportive of new as well as existing trade agreements.…”
Section: Public Opinion and Tradementioning
confidence: 70%
“…Protests have certainly influenced perceived opinion, and trade policy officials are addressing some of the concerns raised by civil society organizations, which is no doubt wise. 3 Yet many elites may have misperceived the state of mass opinion, something that is quite common in the area of international affairs (Kull and Destler 1999;Kull and Ramsay 2000;Page and Barabas 2000;Clark et al 2000). Our data show that the permissive consensus on trade continues and that mass opinion is supportive of new as well as existing trade agreements.…”
Section: Public Opinion and Tradementioning
confidence: 70%
“…With a few exceptions (Clark et al 2000;Weissberg 2001), scholars employing rigorous opinion research techniques and sophisticated analytical approaches increasingly have converged on the position that mass views in the United States, including foreign policy attitudes, are systematically linked, more stable, and less isolationist than previously thought (Caspary 1970;Achen 1975;Page 1988, 1994;Hinckley 1991;Page and Shapiro 1992;Chittick, Billingsley, and Travis 1995;Holsti 1996). Although Converse (1964) questioned whether an "elegant high order abstraction," such as the liberal-conservative continuum, was available to the mass public, some research has suggested that ideology does provide horizontal structure for more specific attitudes and beliefs (Bjereld and Ekengren 1999).…”
Section: A Comparative Approachmentioning
confidence: 99%
“…Although there are practical limitations about the levels of interest and expertise and the coherence of belief structures that can be expected among mass publics, there is a developing consensus that even in the area of foreign policy beliefs, early theorists and researchers (Lippmann 1922(Lippmann , 1925Bailey 1948;Morgenthau 1948;Markel 1949;Almond 1950;Kennan 1951) overstated the softness and instability of mass opinion. With a few exceptions (Clark et al 2000;Weissberg 2001), scholars employing rigorous opinion research techniques and sophisticated analytical approaches increasingly have converged on the position that mass views in the United States, including foreign policy attitudes, are systematically linked, more stable, and less isolationist than previously thought (Caspary 1970;Achen 1975;Page 1988, 1994;Hinckley 1991;Page and Shapiro 1992;Chittick, Billingsley, and Travis 1995;Holsti 1996). Although Converse (1964) questioned whether an "elegant high order abstraction," such as the liberal-conservative continuum, was available to the mass public, some research has suggested that ideology does provide horizontal structure for more specific attitudes and beliefs (Bjereld and Ekengren 1999).…”
Section: A Comparative Approachmentioning
confidence: 99%